Gemi inşa sanayiinde malzeme planlaması - Bayram, Hurşit Oktay (Fen Bilimleri Enstitüsü, 1996)
Ekonominin her sektöründe kaynakların daha verimli kullanımı için bugüne kadar çeşitli üretim planlama ve yönetim modelleri geliştirilmiştir. Bu modellerin gemi inşaatı gibi, projelerinin planlanması ve programlanması oldukça zor olan bir alana uygulanması ise özel bir çalışma gerektirir, özellikle üretim süresi ve kalitesi alanlarında dünya piyasalarıyla rekabet edebilecek konuma gelinebilmesi, önemli kısıtlardan öncelikle zamanın efektif kullanımıyla mümkün olacaktır.Bu da malzeme planlamanın önemini daha da artırmaktadır. Bu çalışmada öncelikle, MRP (Material Requirements Planning), MRP II ( Manufacturing Resource Planning), OPT (Optimized Production Technology) ve JIT (Just-in-Time) sistemlerinin incelenmesi yapılmıştır. Bu sistemlerin uygulama alanları ve prensipleri doğrultusunda karmaşık gemi inşaatı projeleri için en uygun sentezin oluşturulması amaçlanmıştır. Üretilen nihai ürüne bağlı olarak şekillenen talep yapısı, envanter yönetimince dikkate alınması gereken diğer önemli bir husustur. Kullanılan veya kullanılacak olan envanter sistemlerinin seçiminde talep yapısının bağımlı veya bağımsız oluşu önemli bir kriterdir. Her iki talep yapısında da öğeler içeren gemi inşaatı sektöründe, öncelikle yapılması gereken, envanter öğelerinin ABC analizi ve Kritik Değer analizi gibi mevcut yöntemler ışığında sınıflandırılmasıdır. Talep yapısı ve envanter sınıfı belirlenen öğeler için kullanılacak envanter sistemleri de işletmenin finansal stratejileri doğrultusunda kolayca seçilebilecektir. Herhangi bir üretim ortamında malzeme planlamasının sağlıklı bir şekilde yapılabilmesi için öncelikle mevcut üretim sisteminin analizinin yapılması gerekmektedir. Yapılan analiz doğrultusunda özellikle iç ortamda ön imalat gerektiren malzemelerin hangi koşullarda hangi sahfalardan geçeceği ortaya çıkarılacaktır. Bu da malzeme akış hızı ve planlanma sürecinin önemli bir girdisi niteliğindedir. Yazar tarafından bu çalışmada üretimi tamamlanmış bir dökme yük gemisinin makina dairesi blokları imalatının analizi yapılmış ve belirlenen proseslerin tamamlanma zamanları üretim ortamı içi malzeme planlaması verileri olarak ortaya konulmuştur.

The essence of manufacturing is flow of materials from suppliers, trough plants to costumers, and of information to ali parties about what was planned, what was happened, and what should happen next. This is true regardless of what is made, how and when it is made, and who makes it where. The First Law of Manufacturing is, 'Ali benefits will be directly proportional to the speed of flow of materials and information' [1]. This is a universal law applying to every type of manufacturing. Difficulties in controlling manufacturing will decrease and planning will become more effective as materials and information flows speed up. The best use of recourses comes from eliminating problems that interrupt ör slow down these flows. Time is most precious resource employed in the manufacturing process. Equal amounts are available to everyone, but time moves relentlessly; it cannot be stored, extended, ör recycled, and wealth can buy no more. VVasting time causes irretrievable loss. Simple, universal logic underlies ali manufacturing and can be represented by six simple question: 1. What is to made? 2. How many, and when are they needed? 3. What recourses are required to do this? 4. VVhich are already available? 5. VVhich others will be available in time? 6. What more will be needed, and when? Business and marketing strategies determine the answers to the first two questions. Intemal company planning and control systems provide ansvvers to the last four. vii in a manufacturing environment, material management is inseparable from production planning. The function of material management is to translate the overall plan of production into the detailed component requirements and order. Its outputs are both purchasing and manufacturing activities, providing requisition ör orders authorizing them. An ordinary material planning program recommends order priorities and makes capacity requirements planning poşsible, assuming that adequate capacity will be available when required. it does considerably more than merge inventory; it is the heart of the logistic planning. MRP - Material Requirements Planning Manufacturers of large, complex equipment (for example, ships, planes, generators) have long future horizons covered with firm orders. Calculation of gross requirements for majör components of their products and time-phasing these are very difficult without using any computer-based system. Material requirements planning (MRP) is a computer-based production planning and inventory control system. it is also known as 'time- phased requirements planning'. MRP is concemed with both production scheduling and inventory control. it provides a scheduling (priorities) system, an efficient material control system, and a rescheduling mechanism for revising plans as changes occur. it keep inventory levels at a minimum while assuring that required materials are available when needed [2]. Since a large number of manufacturing companies could now afford computers and could benefit from using MRP, it became economically feasible for softvvare companies to develop and market standard MRP packages which could be sold to companies wanting to implement MRP. MRP II - Manufacturing Resource Planning it is clear that the overall problem is not production problem, it is a company problem. VVith this realization more and more companies were shifting to marketing-oriented position, MRP II ör manufacturing recourses planning is used instead of MRP. Under MRP II the entire company's efforts are considered and the computer is used to analyze corporate plans and solve problems. MRP II starts with a company's business plan in which overall objectives are viii defined. These plans are translated into sales objectives by product line. Sales objectives are then translated into forecasts of top level items. Over the next several years MRP II systems will expand the address the often neglected functions such as product service, quality control, human recourses and so on. Today's information systems fully integrates manufacturing functions with marketing and financial data, and contains enough information to run an entire company [3]. OPT - (Optimized Production Technology) OPT has generated considerable interest as a production planning and scheduling tool. OPT can be viewed as an alternative to a comprehensive MRP system in that it provides a complete system for production planning, material planning and resource scheduling. OPT requires a complete description of the production system to operate. The product network has information similar to what would be contained in the bill of materials and routing files for a conventional MRP system. The difference is that the information is combined, using a network structure, into a single file [4]. The production modeling capability of OPT is very complete, allowing the specification of desired stock levels at each operation, maximum stock limits, minimum batch quantities, auxiliary machines and scheduled delays. In addition, specifications of order quantities and due dates are entered in the network. In OPT systems, a module called SERVE by Creative Output Inc. (CO I) uses information of product network and resource description, which is similar to traditional MRP logic, for an initial analysis. The purpose of this initial SERVE analysis the identification of critical bottleneck resources. The idea behind the OPT philosophy is that the importance of effective utilization of critical bottleneck resources directly increase the total output productivity. Just-in-Time (JIT) The just-in-time (JIT) is used in repetitive manufacturing [2]. It is fundamentally an idealized manufacturing philosophy where a comprehensive set of internal and external conditions must be satisfied in IX order for it to be implemented in a manufacturing operation with complete integrity [5]. For JIT to be feasible, the preconditions are uniform plant loading, group technology, quality control at the source (zero defects), minimized setup time, a Kanban type production control system, and local suppliers. JIT a philosophy of production where inventory is considered undesirable. A key ingredient of the JIT process is gradualism. It favors simple operating techniques to improve the manufacturing process gradually rather then relying on bigger and better equipment to improve competitive position sporadically [6]. Kanban - a Japanese word meaning card - is an example of the Toyota philosophy which is to provide management by sight or visual control everywhere possible. This is done through color, light boards, hook boards, charts and graphs at any opportunity. These visual controls facilitate immediate identification of problems such as storage or excess of parts as well as any other unusual occurrence. The use of Kanban is essentially a production management information system through which the 'pull' system of production control is accomplished [7]. Kanban cards are basically in two kinds. One is called the production order Kanban or production Kanban. The other is called the withdrawal or conveyance Kanban. The production Kanban authorizes the preceding process to produce the number of parts or subassemblies that are listed on the Kanban. The conveyance Kanban is attached to a parts container when it is removed from the preceding operation and transported to the next operation. Inventory Management The control and maintenance of inventory is a problem common to all organizations in any sector of the economy. The problems of inventory do not confine themselves to profit making institutions. The total investment in inventory represents a sizable portion of the gross national product. A review of American industry balance sheets reveals at large percentage of the assets in a company lie in inventories. Poor control of inventory can create a negative cash flow, tie up large amounts of capital, limit the expansion of an organization due to lack of capital, and reduce the return on investment by broadening the investment base. Inventories are kind of lubrication for the supply-production- distribution system that protects it from excessive friction. Inventories isolate one part of the system from the next to permit each to work independently, absorb the shock of forecast errors, and permit the effective utilization of resources when demand undulations are experienced [2]. The objective of inventory management is to have the appropriate amounts of raw materials, supplies, and finished goods in the right place, at the right time, at low cost. Inventory cost result from action or lack of action of management in establishing the inventory system. Production system can be classified according to the manner in which demand is supplied and impact the related supply method has on inventory requirements [2] : 1. Production to order. 2. Production to stock. With production to order, no production is initiated until a firm demand for an item exists. With production to stock, production commences in anticipation of demand. Continuous demand items tend to be associated with production to stock as end items produced for finished good inventory. Discrete demand items characteristically are linked to production to order as row materials, parts, and components required to produce customer-ordered demand items. The choice of an inventory system is predicated on whether the items to be controlled have dependent or independent demand patterns. It is a mistake to use systems designed for independent demand items to control dependent demand items and viceversa. However, this should not be construed as an either or decision for inventory system adaptation. Since organizations, may have item from both demand classification, successful ones will use systems in partnership. Distinct systems may be selected to control different demand categories of items, but the system operating conjointly would be used to manage to entire inventory of organization. The systems are designed to be coplemantry. Production Analysis In manufacturing environments (internal), the speed of material flow depends on the lead times of each manufacturing stages. For reliable material planning in any manufacturing environment, it has priority that existing manufacturing system to be analyzed. It is determined how the conditions and stages to be processed for materials that requires prefabrication especially in internal environment in the direction of the analysis done. This is an important input for the material flow speed and planning process. xi Nowadays ships are built by means of assembling outfitted sections. Dimension of the sections are determined with considering shipyard conditions such as lifting capacity, workshop dimensions, etc. Each section is manufactured as a result of some similar serial and parallel performed activities. This similarity of manufacturing a outfitted unit assembly makes easy to assigning of alphanumerically codes (A, B,..., U) for each stage [11]. In this case, the question of "When it is ready ?" is answered. Purchasing and Procurement The role of purchasing and procurement in modern organizations has increased substantially in the few decades. Material costs are frequently the largest proportion of a product's total cost. Inflation, shortages, and unstable markets make purchasing decisions important influences on overall performances of an organization. The typical steps involved in the purchasing process include [2]; 1. Obtaining information on products and their specifications, 2. Finding suitable suppliers, 3. Obtaining competitive bids or negotiating with suppliers, 4. Analyzing bids and proposals, 5. Preparing purchase orders, 6. Expediting and following up orders, 7. Verifying proper receipts of materials and invoice validation, 8. Processing claims, 9. Disposing of surplus materials and equipment. The goal should not be to operate the purchasing department at the lowest cost. It should be attain organizational objectives at the lowest cost.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1996
Keywords: Gemi Mühendisliği; Malzeme planlaması; Marine Engineering; Material planning